Impact of infection in patients with non-ST elevation acute coronary syndrome undergoing percutaneous coronary intervention: insight from a multicentre observational cohort from China - Chen, Peng-Yuan; Liu, Yuan-Hui; Duan, Chong-Yang; Jiang, Lei; Wei, Xue-Biao; Guo, Wei; Chen, Ji-Yan; Tan, Ning; He, Peng-Cheng; Chen, Ji-Yan; He, Peng-Cheng; Liu, Yuan-Hui; et al. (BMJ open, 2020)
ObjectiveWe aimed to describe the association between in-hospital infection and prognosis among patients with non-ST elevation acute coronary syndrome (NSTE-ACS) who received percutaneous coronary intervention (PCI).DesignThis observational cohort originated from a database of patients with NSTE-ACS who underwent PCI from 1 January 2010 to 31 December 2014.SettingFive centres in South China.ParticipantsThis multicentre observational cohort study consecutively included 8197 patients with NSTE-ACS who received PCI. Only patients with adequate information to diagnose or rule out infection were included. Patients were excluded if they were diagnosed with a malignant tumour, were pregnant or presented with cardiogenic shock at the index date. Patients were grouped by whether they had in-hospital infection or not.Primary and secondary outcome measuresThe primary outcome was all-cause death and major bleeding during hospitalisation. The secondary outcomes included all-cause death and major bleeding during follow-up and in-hospital myocardial infarction.ResultsOf the 5215 patients, 206 (3.95%) acquired infection. Patients with infection had a higher rate of in-hospital all-cause death and major bleeding (4.4% vs 0.2% and 16.5% vs 1.2%, respectively; p<0.001). After adjusting for confounders, infection remained independently associated with in-hospital and long-term all-cause death (OR, 13.19, 95% CI 4.59 to 37.87; HR, 2.03, 95% CI 1.52 to 2.71; p<0.001) and major bleeding (OR, 10.24, 95% CI 6.17 to 16.98; HR, 5.31, 95% CI 3.49 to 8.08; p<0.001). A subgroup analysis confirmed these results.ConclusionsThe incidence of infection is low during hospitalisation, but is associated with worse in-hospital and long-term outcomes.